OP0275 Prevalence of Ultrasound-Detected Findings in Foot in Juvenile Idiopathic Arthritis versus Healthy Children: Association To Paediatric Foot Posture. (15th July 2016) - Collado, P.; Gonzalez, M.L.; Alcalde, M.; Calvo, C.; Diaz-Delgado, R.; Morales-Lozano, R.
Abstract : Background: Foot problems have been reported in several JIA categories, even though children rarely complain symptoms. Besides synovitis, peri-articular manifestations have been associated with reduced joint ranges-of-motion and deformities. Musculoskeletal ultrasound (US) is more sensitive than clinical examination for detecting signs of inflammation. It becomes an accessible tool with an ongoing role on the foot care in JIA. Consequently, the clinical relevance of what is considered as a normal or pathological US finding needs to be more precisely clarified. Objectives: 1. To determine and to compare prevalence of US-detected findings in JIA patients and healthy children. 2. To examine associations of foot US-findings to foot abnormalities using objective podiatry assessment. Methods: Eighty-four children (168 feet), 29 children with a definitive diagnosis of JIA (ILAR criteria) and history of foot/ankle complains were recruited from the outpatient paediatric rheumatology clinic at our Hospital as well as 55 healthy children. The participants underwent clinical, podiatrist and US assessment. The sonographer, who was blinded to the clinical and podiatrist details, performed gray- scale and power Doppler (PD) bilateral evaluation at each site of study (8 joints, 8 tendons and 2 entheseal insertions per foot). Joint recess distension, tenosynovitis, abnormal echogenicity or thickening of entheseal insertion, and PD signal were assessment (dichotomous score: absence or presence). The podiatry assessment included the following measures: 1) footprint evaluation on podoscope, 2) the calcaneus relaxed position test (RCSP), 3) the foot postural index (FPI-6), 4) the standing heel-rise test (SHRT) the Jack test or Hubscher maneuver. Results: The JIA group included 17 girls and 12 boys (mean age, 9.3 ± 4.6 years old), oligoarthritis was the commonest category and disease duration was 53.4 ± 49 months. No statistical differences were found for demographic characteristics between the two groups. Forty-six children had at least one US abnormality (20, JIA and 26, control). Distension of the dorsal recess in the first metatarsophalangeal (MTP1) was the most frequently detected finding (32 JIA feet and 46 controls; 52% and 41.8% of feet in each group respectively) without statistical differences (p>0.05). The presence of distension of the anterior tibiotalar joint (TA) and anterior subtalar joint was always associated with the presence of disease. The presence of tenosynovitis and enthesitis was associated as well. The podiatry assessment showed several findings: joint hypermobility of MTF1was frequently detected in the study population, mostly in JIA (p=0, 001), and the association between abnormal FPI/ footprint and US findings (distension of the anterior subtalar and MTP2 joints) (p<0.05). Conclusions: This study describes the prevalence and location of US findings in the paediatric foot. Distension of the MTP1 joint was quite common in childhood and it was associated to joint hypermobility. FPI seems to be associated with the presence of anomalies of TA, subtalar and MTP2 joints in children with JIA. Further studies are needed to confirm these results. Disclosure of Interest: None declared